2012
DOI: 10.1182/blood-2011-06-354647
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK inhibition suppresses the TLR-hypersensitive phenotype in FANCC- and FANCA-deficient mononuclear phagocytes

Abstract: Fanconi anemia, complementation group C (FANCC)-deficient hematopoietic stem and progenitor cells are hypersensitive to a variety of inhibitory cytokines, one of which, TNF␣, can induce BM failure and clonal evolution in Fancc-deficient mice. FANCC-deficient macrophages are also hypersensitive to TLR activation and produce TNF␣ in an unrestrained fashion. Reasoning that suppression of inhibitory cytokine production might enhance hematopoiesis, we screened small molecules using TLR agonist-stimulated FANCCand F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 53 publications
13
58
0
Order By: Relevance
“…Indeed, a recent study was designed to find inhibitory molecules able to reduce the production of TNFα in FA patients and, therefore, retard the patients' progressive bone marrow failure. 8 In the present study, we found evidence of overexpression of STAT1 in FANCA-deficient cells and how this may explain the hypersensitivity of FA-A cells to both genotoxic agents and to inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, a recent study was designed to find inhibitory molecules able to reduce the production of TNFα in FA patients and, therefore, retard the patients' progressive bone marrow failure. 8 In the present study, we found evidence of overexpression of STAT1 in FANCA-deficient cells and how this may explain the hypersensitivity of FA-A cells to both genotoxic agents and to inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 62%
“…[4][5][6] Thus, two different mechanisms are nowadays considered to participate in the bone marrow failure of FA patients: on the one hand, FA cells accumulate DNA damage in each division, which results in exacerbated p53 activation and apoptosis of their hematopoietic progenitors 7 and, on the other hand, FA patients overproduce inhibitory cytokines, which eventually degrade their bone marrow. 8 Signal transducers and activators of transcription (STAT) are transcription factors activated by phosphorylation triggered by ligand-bound cell surface receptors. STAT factors mediate signaling initiated by many extracellular stimuli including cytokines and growth factors and induce responses such as cell proliferation, differentiation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The development and culture conditions of the derivative cell lines we established (T-shNT, T-shFA, and T-shFC) were described previously. 16,17 BM-derived macrophages (BMDM) from wild-type and Fancc 2/2 mice were prepared as described previously. 17 Murine macrophages were cultured at a concentration of 50 000 cells per mL for 24 hours in RPMI 1640 medium (Life Technologies, Carlsbad, CA) with 10% fetal bovine serum (FBS; Thermo Scientific Hyclone, Logan, UT) in the presence of the indicated doses of R848.…”
Section: Cell Lines and Primary Cellsmentioning
confidence: 99%
“…16,17 BM-derived macrophages (BMDM) from wild-type and Fancc 2/2 mice were prepared as described previously. 17 Murine macrophages were cultured at a concentration of 50 000 cells per mL for 24 hours in RPMI 1640 medium (Life Technologies, Carlsbad, CA) with 10% fetal bovine serum (FBS; Thermo Scientific Hyclone, Logan, UT) in the presence of the indicated doses of R848. All murine studies were approved by the Portland Veteran's Administration Institutional Animal Care and Use Committee.…”
Section: Cell Lines and Primary Cellsmentioning
confidence: 99%
See 1 more Smart Citation